Soil Fertility Management in Coastal Areas through Organic Amendments with Different C/N Ratios: Evidence from Local Palu Shallot Cultivation - Lisa Indriani Bangkele; Idris; Kasman Kasim; Sjarifuddin Ende; Siti Fathurahmi Wahid; Nur Aisyah; Nilsa (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
Lembah Palu shallot is a high-value local horticultural commodity of Central Sulawesi, its adapted to the dry lowland climates makes it a promising crop for coastal agriculture. Agricultural development in coastal areas requires soil-management technologies that improve nutrient availability, enhance the rhizosphere environment, and sustain crop productivity. This study evaluated the effects of organic amendments with different carbon-to-nitrogen ratio (C/N ratio) on soil pH, rhizosphere microorganism populations, nitrogen (N), phosphorus (P), and potassium (K) acquisition, and the yield of Lembah Palu shallot. A one-factor randomized block design was used with five treatments: unamended control, cattle manure (C/N 19.8), rice husk (C/N 40.7), cocopeat (C/N 90.6), and vegetable compost (C/N 13.5). The measured variables included soil N, P, and K; plant-tissue N, P, and K acquisition; rhizosphere microorganism colony numbers; bulb numbers; fresh and oven-dry bulb weights; and yields per hectare. The results demonstrate organic amendments with different C/N ratio influenced soil nutrient dynamics, rhizosphere microorganism abundance, plant-tissue nutrient concentrations, and yield of Lembah Palu shallot. Among the amendments evaluated, cocopeat (C/N 90.6) produced the highest tissue N concentration (3.57%), bulb number (8.50 bulbs clump⁻¹), bulb dry weight (0.09 g clump-1), numerical fresh bulb yield (5.87 t ha⁻¹), and oven-dry bulb yield (0.05 t ha⁻¹), significantly higher than cattle manure and vegetable compost treatments. The favorable performance and characteristics of cocopeat could associated with gradual nutrient release and improved root-zone conditions, particularly water retention and aeration, which can enhance nutrient acquisition in porous coastal soils. Because cocopeat is derived from locally available coconut residues, its use may also support agricultural-waste utilization and sustainable agriculture in coastal areas.